2021
DOI: 10.1039/d0ta09228b
|View full text |Cite
|
Sign up to set email alerts
|

A gel-limiting strategy for large-scale fabrication of Fe–N–C single-atom ORR catalysts

Abstract: Although transition metal single atom site catalysts (SASCs) show great potential in electrocatalysis, their large-scale controllable and flexible preparation remains a great challenge. In this article, we report a simple...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Nevertheless, the inductively couple plasma‐optical emission spectrometer (ICP‐OES) analysis showed that the Fe content in the Fe−N−C/700 was about 0.29 wt %, confirming that the presence of Fe element. In Figure 2d, the N 1s spectra of Fe−N−C/700 could be deconvoluted into five characteristic peaks, which can be well assigned to pyridinic N (398.2 eV), Fe−N (399.2 eV), pyrrolic N (400.2 eV), graphitic N (401 eV) and oxidized N (402.3 eV) [40,41] . The calcination process played an important role to determine the composition of N 1s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the inductively couple plasma‐optical emission spectrometer (ICP‐OES) analysis showed that the Fe content in the Fe−N−C/700 was about 0.29 wt %, confirming that the presence of Fe element. In Figure 2d, the N 1s spectra of Fe−N−C/700 could be deconvoluted into five characteristic peaks, which can be well assigned to pyridinic N (398.2 eV), Fe−N (399.2 eV), pyrrolic N (400.2 eV), graphitic N (401 eV) and oxidized N (402.3 eV) [40,41] . The calcination process played an important role to determine the composition of N 1s.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 2d, the N 1s spectra of FeÀ NÀ C/700 could be deconvoluted into five characteristic peaks, which can be well assigned to pyridinic N (398.2 eV), FeÀ N (399.2 eV), pyrrolic N (400.2 eV), graphitic N (401 eV) and oxidized N (402.3 eV). [40,41] The calcination process played an important role to determine the composition of N 1s. After analyzing the relative contents of doped N in FeÀ NÀ C/700-Pre (Figure S3d) and FeÀ NÀ C/700, it can be found that the proportion of pyridinic N decreased, while the content of FeÀ N species increased from 7.03 % to 11.88 % after the secondary pyrolysis, strongly indicating part of pyridinic N was converted to the FeÀ N coordination (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…28 Second, the materials must be synthesized reproducibly and in large quantity, to enable extensive fundamental investigations and to allow for commercial scale-up. Most current syntheses of Fe-N-C SACs yield catalytic powders on the ten milligram scale, 12,18,20,21,[29][30][31][32][33][34][35][36] whereas a hundred gram scale is needed to power automotive fuel cell stacks at current performance levels. [37][38][39] Large scale syntheses of Fe-N-C materials have been reported recently, 40,41 albeit relying on commercial activated carbons, rich in micropores yet lacking signicant owenhancing meso-or macroporosity.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the electrocatalytic performance of CNFs can be elaborately engineered through three ways: (i) doping heteroatoms, (ii) introducing transition metals, and (iii) controlling the pore structure. The introduction of defects by doping heteroatoms can regulate the charge environment of carbon materials and reduce the activation energy barrier of substrate molecules. , Wu et al successfully fabricated N, F, P ternary-doped CNFs by electrospinning, which showed considerably enhanced bifunctional oxygen electrocatalysis activity . In addition, the electronic structure of the transition-metal center is instrumental in breaking the OO bond and the subsequent oxygen reduction. , Xia et al used electrospinning and pyrolysis methods to encapsulate highly dispersed and active iron carbide nanoparticles in multichannel hollow nanofibers with high electrical conductivity and porous structures to prepare efficient and stable electrocatalysts . Furthermore, adjusting the pore structure of CNFs to increase the specific surface area is another effective method to enhance the electrocatalytic capability .…”
Section: Introductionmentioning
confidence: 99%
“…28 In addition, the electronic structure of the transition-metal center is instrumental in breaking the OO bond and the subsequent oxygen reduction. 29,30 structures to prepare efficient and stable electrocatalysts. 31 Furthermore, adjusting the pore structure of CNFs to increase the specific surface area is another effective method to enhance the electrocatalytic capability.…”
Section: ■ Introductionmentioning
confidence: 99%